Chemical Reaction Engineering I: Manual for Performing Laboratory Exercises - Pečar, Darja (2025)
Manual for performing laboratory exercises in the course Chemical Reaction Engineering I represents a teaching aid for students to be able to approach experimental work in the laboratory.
Keywords: chemical reaction engineering; batch reactor; continuous reactor; kinetic parameters; activation energy